Hot spot : North America and Europe - Rudolph, Joseph R. (Joseph Russell), 1942- (Hot spot histories., 2008)
From the Publisher: Even in the relatively serene world of North America and Western Europe, numerous conflicts with the propensity for sustained political violence are carried out by domestic groups with alarming regularity. This in-depth volume explores conflicts and potential hot spots in these areas, from anti-globalization protests to immigration politics to the Basque Provinces and the ETA. Coverage is divided into three regions-the established democracies of the U.S., Canada, and Western Europe; the democratizing countries of post-communist Europe; and the more volatile region encompassing Russia, the Balkans, the Caucasus, and Post-Soviet Eastern Europe-for a greater understanding of geographic interrelationships. With regional chronologies of events, a print and nonprint bibliography, and engaging photos, this comprehensive volume is a first-stop reference source for the most significant political, cultural, and economic conflicts in North America and Europe today.